Androgen Receptor Expression In Benign Prostatic Hyperplasia And Prostate Cancer - Anandia Putriyuni; Nana Liana (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Benign prostatic hyperplasia (BPH) and prostate cancer (PCa) require androgen/androgen receptor (AR) signals. It plays an important role in the development of BPH; the initiation, growth, and progressivity of PCa, but the mechanism of AR in both of them remains unclear.Objective: This study aims to evaluate the expression of AR in BPH and PCa. Methods: Analytical study with cross-sectional design on a sample of 56 cases of BPH and PCa, respectively. The sampling was from the Anatomic Pathology laboratory in West Sumatera. Immunohistochemical (IHC) staining of AR to analyze protein expression semi-quantitatively. High expression of AR was set as strong interpretation. Results: Mostly AR expression was high in BPH at 98.21% (55 cases) whereas high AR expression of PCa in tumor cells was slightly more in 51.79% (29 cases) than low AR expression. Most cases of PCa were Gleason score 9, namely 25 (44.64%) cases, and high AR expression in 29 (51.79%) cases. High-grade Gleason score (Gleason score 8-10) with high AR expression was more than low-grade Gleason score (Gleason score ≤ 7). There was a statistically significant association between AR expression and Gleason score (p=0.018).Conclusion: Activation of AR pathway is crucial for the development and progression of BPH and PCa. High AR expression was revealed most in epithelial and stromal cells of BPH, but it showed half of the tumor cells in PCa. The AR expression in tumor cells of PCa should be examined in cases to determine patient prognosis.